Lettuce (Lactuca sativa) production with effluent from a tilapia culture maintained in bft and low salinity Produção de alface (Lactuca sativa) em efluentes de um cultivo de tilápias mantidas em sistema bft em baixa salinidade - Lenz G.L. (2017)
© 2017, Instytut Technologii Drewna. All rights reserved.This experiment evaluated the effect of salinity on growth performance of different lettuce cultivars (Lactuca sativa) in an aquaponics system with biofloc technology. The device contained two independent systems with two different salinities 0 ppt and 3 ppt. Were stored, Juvenile tilapia (Oreochromis niloticus) 6.1 kg m-3 and three varieties of lettuce: red leaf, smooth and crisp 20 plants m-2 in the floating system. All fish performance parameters showed no statistical differences, except for the hepatossomatic index, higher in 3 ppt (4.35%) versus (3.07%) in 0 ppt (P<0.05). In general, the productivity of lettuce cultivars were superior in fresh water (1.21 kg m-2) compare to brackish water (0.8 kg m-2) (P<0.05). In most phytotechnical parameters evaluated, the purple variety had better performance than the smooth and crisped varieties. In relation to plant quality index (IQP), purple variety in brackish water had the best score, presenting leafs with higher integrity and intense coloration. The results demonstrated that it is possible to integrate the production of red leaf variety in aquaponics systems with the technology of bioflocs in low salinity.